PERGOLAKAN ANTARA LIFE STYLE DAN SYARI’AT-BUDAYA DALAM KEHIDUPAN PEREMPUAN ACEH MASA KINI - Abdul Wahid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
Acehnese women life in the demands of the implementation of Islamic law and Aceh cultural context. The development of today's lifestyle demands the women in Aceh to maintain these two patterns. There are a lot of women in Aceh have a strong commitmentto keep the pattern of their life as an